Factors influencing reproductive efficiency and pregnancy in Pura Raza Española mares - A. Akourki; A. Echegaray; M.V. Falceto; O. Mitjana (Veterinární Medicína, 2017)
The aim of this study was to analyse ovarian activity and pregnancy in 140 Pura Raza Espanola mares over a period of two consecutive years. The data were analysed using SPSS software to evaluate the effects of age, category of mares and season on pre-ovulatory follicle size, ovulation rate, interval from foaling to pregnancy, gestation length, incidence of twin pregnancies and pregnancy losses. The results showed that follicular diameter was significantly (P < 0.05) smaller in fillies (3-year-old) and maiden mares than in older and multiparous mares. Within the group of animals treated with gonadotropin hormone hCG, 87.23% ovulated 48 h following administration. Length of gestation varied from 305 to 356 days and all gestation pregnancies of less than 305 days resulted in a non-viable foal. In addition, foaling season affected (P < 0.05) the post-partum conception interval and the length of gestation, which were shorter and longer in the winter foaling, respectively. Regarding the other parameters, mares of this stud exhibited relatively very low rates of double ovulations, twin pregnancies and pregnancy losses. We conclude that age and category of mares and foaling season influence fertility and foaling rates by affecting pre-ovulatory follicle size, pregnancy loss and gestation length.